Impacts of inequalities in utilization of key maternal health service on fertility preference among high parity women in four selected regions of Ethiopia - Tigist Shumet; Nigatu Regassa Geda (BMC, 2024)
Abstract Background Fertility is one of the three main components which determines the size, structure, and composition of a population, and fertility preferences are important measures for forecasting fertility levels of a population. Therefore, this study aims to assess the impacts of the inequalities in the utilization of key maternal health services on fertility preference among high parity women in four selected regions (i.e., Afar, Beninshangul-Gumuz, Gambella and Somali) of Ethiopia. Methods The study used data collected for the 2016 Ethiopian Demographic and Health Surveys (EDHS) survey. It includes a total of 977 high parity women (104 urban and 873 rural) residing in the four regions of the study. Bivariate logistic regression was used to select the potential variables by using a cut off p-value < 0.2 and then the multivariable logistic regression analyses were performed to assess the association between the selected explanatory variables (i.e., control and exposure variables) and the outcome variable (i.e. fertility preference). Further, the study employed a Population Attributable Fractions (PAFs) to examine the population level impacts of the inequalities in maternal and child health service variables on fertility preference. Results The results showed that religion, household wealth index, place of delivery and contraceptive use were significantly associated with fertility preference. The results of the PAFs analysis indicated that contraceptive use had the biggest impact (80%), meaning that non-use of contraceptive increased fertility preference among women in the four regions. Similarly, out of health facility delivery increased fertility preference by 37%. Conclusion The study findings underscore the critical factors influencing women's fertility preferences in the studied regions. Low utilization of maternal health services had an impact on fertility preference, accounting for more than half of the observed variations in fertility preferences. To address this issue, targeted interventions are recommended: enhancing access to maternal health services, strengthening fertility control programs, promoting the benefits of using these services, and actively addressing inequalities.